FRAUD PENTAGON DAN ANCAMAN KEBANGKRUTAN STUDI PADA PERUSAHAAN PERBANKAN - Nainggolan, Dony (BALANCE: Jurnal Akuntansi, Auditing dan Keuangan, 2022)
The purpose of the study was to determine the effect of the fraud pentagon on the threat of bankruptcy in banking companies listed on the Indonesia Stock Exchange in 2018-2020. The fraud Pentagon consists of five indicators namely external pressure, effective monitoring, auditor turnover, director turnover and the number of frequent CEO photos. While the threat of bankruptcy is measured by the X-Score. The method of data analysis is descriptive and hypothesis testing using multiple linear regression analysis. The research sample is 122 financial statements from 42 banking companies listed on the Indonesia Stock Exchange in 2018-2020. The results showed that external pressure variables and changes in auditors had an effect on the threat of bankruptcy. While the variables of effective supervision, the change of directors and the number of CEO photos that often have no effect on the threat of bankruptcy